A novel player: cyclosporine therapy in the management of inflammatory bowel disease - Weissman, Simcha; Chris-Olaiya, Abimbola; Mehta, Tej I.; Aziz, Muhammad; Alshati, Ali; Berry, Rani; Fatima, Rawish; Kolli, Sindhura; Hassan, Ammar; Sciarra, Michael A. (Translational Gastroenterology and Hepatology; Vol 4 (September 2019): Translational Gastroenterology and Hepatology, 2019)
Amongst other indications, cyclosporine therapy has emerged as a novel agent for the management of severe refractory ulcerative colitis (UC). In the historic population of patients receiving cyclosporine therapy—namely solid organ transplant patients—renal toxicity has proven to be a significant mitigating side effect limiting the therapeutic window. However, dose-limiting sequelae amongst patients receiving cyclosporine for inflammatory bowel disease (IBD) have not been as significant. As a result, the fear of renal toxicity as an adverse effect is less of a concern in IBD patients. The goal of this manuscript is to emphasize the need for future research to explore optimal drug dosing and extended use of cyclosporine therapy in the treatment of IBD—given its pathophysiology, efficacy, and safety profile in patients with IBD.